RESEARCH OF STRUCTURE AND DYNAMICS OF THE MARKET OF AIR TRANSPORTATION IN RUSSIA - A. Zinchenko (Вестник университета, 2017)
In article the complex research of a condition of the domestic market of air transportation is conducted. By results of the carried-out analysis distribution of the market of aircrafts on regions, a share of the Russian aircraft companies in the world volume of air transportation, the loudspeaker and growth rates of a passenger turnover and goods turnover and also distribution of volume of air transportation on types of aircrafts is shown. The carried-out analysis showed that growth rates of air transportation in the Russian segment of the market remain above the average world indicators.